Introductory Peripheral Nervous System Review Games for Preclinical Learners (Out of Print) - Frank Reilly; Edwin Allen; Allison Reed; Jeffrey Altemus (Association of American Medical Colleges, 2009)
Abstract This module contains five Jeopardy-style interactive computer games that were developed to provide beginner health professional learners with drill-and-practice exercises evaluating peripheral nervous system knowledge acquisition and retention. The objective for creating the courseware was to stimulate self-directed and problem-based learning in the format of NBME anatomy subject examinations. The rationale was to integrate related disciplines into a structured format that is readily accessible for local and distance learning, as well as self-assessment. The courseware is user friendly and achieves a dimension that cannot be attained by using conventional examination review books. Since implementation of the courseware in 2001, 8% more students score correct answers on written exam questions. Learner surveys rate the "wired" games as the third highest among the resources provided for the human structure course. Virtual patients and patient cases were ranked first and second, respectively. Organizing content into discrete tutorials is highly effective in teaching learners a large volume of information without overwhelming them all at once. Exposing preclinical students to interactive games motivates learning and enhances memory. The learner is not a passive observer, but instead, a participant engaged in a performance-based activity. Framing review games in a clinically relevant manner not only serves to solidify what students have learned in their courses, but also creates confidence by demonstrating how they will approach patient problems in their clinical years. These observations are supported by recent improvements in learner performance on block and subject shelf exams.